Dimensions in Attitudes Toward the Aged - Signori, Edro I.; Butt, Dorcas Susan; Kozak, John F. (Canadian Journal of Counselling and Psychotherapy, 2012)
A description of attitudes toward the aged is based on a factor analysis of ratings by 456 participants, aged 14 to 40, on 69 bipolar variables. The five major dimensions emerging and subsequently used to describe the aged are: Integrity, Fortitude, Social Appeal, Dependableness and Open-mindedness. Initial ratings on the 69 variables arc, for the most part, strongly in the socially desirable direction yielding a very positive portrait of the aged. The results suggest a necessary reconsideration of the negative social images of the aged imparted within much literature on gerontology.